Spectroscopic analysis and cytotoxic activity of quas-sinoid isolated from the seeds of Brucea javanicaon Hela cell - Sonlimar Mangunsong; Dwiprahasto I; Mustofa .; Jumina . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
The quassinoids from Brucea javanica exhibit biological activities as antimalarial, antitumor, antiviral and antiamoebic activities. These quassinoids having a promising antitumor activity.This research was aimed to isolated quassinoid (bruceine A, MW 522 g/mol) compound from B. javanica and to investigate the cytotoxicity of bruceine A under invitro conditions in Hela cells. The cytotoxicity assays using MTT assay. The bruceine showed a good cytotoxic activity in Hela cells at 24 hours with doxorubicine as a positive control. Structural elucidation of bruceine is done by using UV and FT-IR spectra, NMR spectra recorded on Tesla av600, (400 MHz) 1HNMR in pyridine (D5), some in Gyro (300 MHz) 1HNMR in acetone-(d6), DMSO-(d6) and CdCl3 ,13CNMR, 75 MHz, mass spectra on biospectrometry LC-MS. Analytical HPLC retention time,tRwas 4.617 minutes (Met/H20) 60:40. Its Molecular formula was determined to be ( C26 H34 O11) by the [M+H]+ ion peak at m/z 523 and m/z 1045 confirmed by High Resolution mass spectra Orbitrap (HRESIMS). From the results demonstrated that could be bruceine A compound refers to our spectral data. Its has activity in IC50 value 191,5 µM on Hela Cells under invitro conditions.Key words: Quassinoid, B. javanica,Brusein A, Spectroscopic, Anticancer